Five-year Survival Rate of Prostate Cancer in Iran: Results of the national cancer-registry system during 2010-2015 - Aliakbari, Fereshte; Ghanbari, Mohammad Ali; Khayamzadeh, Maryam; Hajian, Mohammad Reza; Allameh, Farzad; Ahadi, Mahsa; Sadeghzadeh, Zahra; Akbari, Mohammad Esmaeil; Solimani, Mohammad; Nematollah, Shahrzad (Archives of Men’s Health, 2020)
Background: Prostate Cancer is recognized as the second cause of death due to cancers among men worldwide. Due to the lack of local evidence on the survival rate of patients with prostate cancer, this study aimed to estimate the 5-year survival rate of patients afflicted with this condition in Iran. Materials and Methods: This study made use of information on 9,772 prostate cancer cases who were registered in the National Cancer Registry during 2010-15. A telephone survey, with a response rate of 35%, was conducted to gather additional information such as death status, demographic characteristics, and clinical profile. Kaplan-Meier estimates was used to estimate five-year survival rates. Results: The overall five-year survival rate of prostate cancer was 82% (95% CI: 80-83%). Significantly higher five-year survival rates were observed among retired patients (rate: 94%,95%CI: 92-96), patients receiving a combination of radiotherapy and surgery (rate: 92%,95%CI: 89-94), and patients residing in rural areas (rate: 92%, 95%CI: 90-93). Conclusion: We found that various factors such as occupation, area of residence, and the type of medication, may influence on survival rate of prostate cancer. Careful evaluation and understanding of effective factors are required to adopt proper health policies and treatment options. Due to the importance of etiologic and epidemiological data, inclusion of such data into the national registry system for Prostate Cancer is strongly recommended.